Hubungan Kondisi Rumah dan Kepadatan Lalat di Sekitar Tempat Pembuangan Akhir Sampah - Wispriyono, Bambang; Afrilia, Erza Nur (Universitas Ahmad Dahlan, 2017)
Background: People who live in a poor condition of house or in a bad environment quality can attract flies to thrive and transmit disease. In the protection against disease, the house should have safe and clean facilities and being prevented from vector that has role in transmitting the disease, such as housefly. Residential area in Cipayung village, especially around final waste disposal (TPA) Cipayung, Depok with a radius of 200 meters from the landfill of final waste disposal has the potential to become perching place of housefly, because of flight range of housefly can reach around 200-1000 meters. Method: This research is done by a cross sectional study design that aims to determine relation between house condition with the density of housefly. Results: The results showed that there was no significant relation between house criteria with housefly density inside house with p-value 0.659 (OR 0.7; 95% CI: 0.136 to 3.920), however there is a significant relation between house criteria with housefly density outside house, house with unhealthy house criteria has risk 4.2 times higher houseflies density rather than house with healthy house criteria p-value 0.011, (OR 4.273; 95% CI: 1.414 -12.909). Conclusion: Housefly control can be executed through making healthy housing and environmental.